THE APPLICATION OF THE ROUND ROBIN BRAINSTORMING (RRB) LEARNING MODEL USING DEVELOPMENT STRATEGIES IN INDONESIAN LANGUAGE SUBJECTS FOR CLASS X STUDENTS IN PUBLIC HIGH SCHOOL 1 KAMANG MAGEK AGAM DISTRICT - Istiqlal, Abdul (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
The world of education is currently facing many challenges. Both from the development of science and technology and global economic growth. Therefore, the world of education cannot be made just so it does not follow the applicable rules which are increasingly decreasing the level of quality of education itself. The world of education must be able to foster attitudes and behaviors that are useful for individuals for their future. On the other hand, what is faced by the world of education is where schools as institutions or institutions must be able to provide a pleasant atmosphere. School as an avertive, where students and teachers face various tasks that they must fulfill. Therefore, school-based management is needed which can support the implementation of various learning models and strategies to meet the needs of the curriculum and society. This research tries to find out how the application of the Rond Robin Brainstorming model with development strategies in Indonesian language subjects at SMA 1 Kamang Magek Agam district. This research tries to find out how efforts to apply learning models and learning strategies in an effort to achieve learning outcomes. This research was conducted in the 2023/2024 school year where the research subjects were 24 students and several teachers. This research was conducted in 3 cycles, of which cycle 1) planning, 2) action) and cycle 3) observation and then see if there is no reflection. Data collection techniques by conducting observations and questions. The first meeting with cycle 1 (one) got 64.62%, it can be said that 60% of the success rate. Cycle 2 (two) got 86.42% increased from the first cycle. Furthermore, in cycle 3 (three) got 92.74% almost 100% success in applying the Round Robin Brainstorming (RRB) model and development strategies in Indonesian language subjects. This shows that the research hypothesis can be accepted.